1998
DOI: 10.1002/pro.5560070716
|View full text |Cite
|
Sign up to set email alerts
|

Structure and stability of the P93G variant of ribonuclease A

Abstract: Abstract:The peptide bonds preceding Pro 93 and Pro I14 of bovine pancreatic ribonuclease A (RNase A) are in the cis conformation. The trans-to-cis isomerization of these bonds had been indicted as the slow step during protein folding. Here, site-directed mutagenesis was used to replace Pro 93 or Pro 114 with a glycine residue, and the crystalline structure of the P93G variant was determined by X-ray diffraction analysis to a resolution of 1.7 w.This structure is essentially identical to that of the wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 40 publications
0
24
1
Order By: Relevance
“…This is in sharp contrast to the previous study where the introduction of the two nipecotic acid six-membered rings at position 113 and 114 only increased the DT m by (1.2 6 0.3)8C. RNase has been a focus of protein folding studies by the Scheraga group which have shown multiple folding pathways depending on the redox reagent (DTT versus glutathione) 119,120 or the location of the four disulfide bonds (RNase versus onconase). 119,121 It would be intriguing to analyze the pathways associated with folding of the Pro114dmP mutant.…”
Section: Torsional Entropycontrasting
confidence: 73%
See 3 more Smart Citations
“…This is in sharp contrast to the previous study where the introduction of the two nipecotic acid six-membered rings at position 113 and 114 only increased the DT m by (1.2 6 0.3)8C. RNase has been a focus of protein folding studies by the Scheraga group which have shown multiple folding pathways depending on the redox reagent (DTT versus glutathione) 119,120 or the location of the four disulfide bonds (RNase versus onconase). 119,121 It would be intriguing to analyze the pathways associated with folding of the Pro114dmP mutant.…”
Section: Torsional Entropycontrasting
confidence: 73%
“…19 The discussion centered on generating a construct similar to RNase S, but which explored the role of the C-terminal segment of RNase contributing His119 to the catalytic site. Ultimately, the semisynthetic ribonuclease, RNase-(1-118)- (111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124), was evolved to study the role of the C-terminal segment in recognition and catalysis. [45][46][47][48] A three-component system, combining equimolar amounts of RNase fragments 1-20, 21-118, and 111-124, retained 30% of the enzymatic activity of intact RNase.…”
Section: Complex Of Rnase With C-terminal Segmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is not rote, as replacing Asn113 and Pro114 with R-Nip-RNip (a diastereomer of R-Nip-S-Nip) eliminates enzymatic activity. Similarly, the transition temperatures for the P114A and P114G variants are decreased by $10 C. [23][24][25] Thus, b 2 -hAla-b 3 -hAla and R-Nip-S-Nip are more than passive linkers 26 -both support native protein structure. This conclusion is supported by the indistinguishable CD spectra of both RNase A and b 2 b 3 hAla RNase A (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 93%